SIKLUS HIDUP BISNIS KELUARGA - Rofiah, Chusnul; Ransimanti Yuvati (Universitas Dr. Soetomo, 2024)
The internal dynamics of business families show that family firms are unique in their learning opportunities and educational needs for various reasons: (1) the long time span of family involvement in the business (2) the participating parties have different interests and roles for each to play. in companies and families everything is important to the company's functioning of the business (3) members of the same family work together, they may experience strong emotions from filial love and parental altruism, to personal hostility stemming from early sibling rivalry. The focus of our research is on concentrating on matters of complexity and scale, where the family plays a major management and ownership role, and where there is an intention to do so maintain constancy within the family. With a phenomenological approach and the object of our research is a gold shop in Jombang which has reached 3 generations and was founded in 1948. Using manual data analysis procedures, this research found that in maintaining the life cycle of a family business there are two main points: (1) family business managed by family members and in important positions, familiar with the business environment so that generational transfer can be prepared gradually, without coercion and careers proceed according to indirect procedures at the top level. (2) a marketing strategy which requires flexibility in work patterns, time and network expansion. Apart from that, it must also keep up with the times by prioritizing customer satisfaction so that it will create positive communication and don't forget to innovate by not carrying out centralized control and must maintain a good name.